2021
DOI: 10.1149/1945-7111/ac1d02
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Flower-Like, Hyperbranched Na3FePO4CO3 Nanocrystals and Their Electrochemical Performance as Cathodes in Aqueous Rechargeable Sodium-Ion Batteries

Abstract: Aqueous rechargeable sodium-ion batteries (ARSBs) have received much attention due to their low cost, the vast abundance of sodium, and the possible application for a smart grid-scale energy storage system. Here, we synthesized Na3FePO4CO3, a cathode material for ARSBs by a low-temperature ionothermal method using deep eutectic solvent and investigated its electrochemical performance. The physical characterization of the synthesized cathode material was done using X-ray diffraction, scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Na 3 FePO 4 CO 3 only provides a voltage plateau of 2.7 V, which significantly limits the corresponding energy density. [ 99 ] Manjunatha et al [ 100 ] employed Na 3 FePO 4 CO 3 for superior performance in aqueous rechargeable SIBs, which demonstrates the application of Na 3 FePO 4 CO 3 in aqueous batteries. Sadrnezhaad et al [ 101 ] prepared Na 3 MnPO 4 CO 3 by modified Hummers method, as shown in Figure 18c.…”
Section: Mixed Phosphatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Na 3 FePO 4 CO 3 only provides a voltage plateau of 2.7 V, which significantly limits the corresponding energy density. [ 99 ] Manjunatha et al [ 100 ] employed Na 3 FePO 4 CO 3 for superior performance in aqueous rechargeable SIBs, which demonstrates the application of Na 3 FePO 4 CO 3 in aqueous batteries. Sadrnezhaad et al [ 101 ] prepared Na 3 MnPO 4 CO 3 by modified Hummers method, as shown in Figure 18c.…”
Section: Mixed Phosphatesmentioning
confidence: 99%
“…Reproduced with permission. [ 100 ] Copyright 2021, American Chemical Society. b) Charge/discharge curves of Na 3 FePO 4 CO 3 at 10 mA g −1 .…”
Section: Mixed Phosphatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al recently prepared a Na 3 FePO 4 CO 3 by the mechanical balling process, which delivers a more extensive discharge capacity of 159 mAh g −1 (1.66 mole Na per formula) at 60 °C. [ 97 ] For the relatively low operation potential (2.6 V vs Na/Na + ), restrict its energy density at cell level in the non‐aqueous electrolyte, Shiprath et al extended applications of Na 3 FePO 4 CO 3 cathode in aqueous SIBs, which exhibited impressive electrochemical performance. [ 98 ] The carbonate phosphates with two electronic reactions per formula theoretically provide high capacity, but the Na diffusion kinetics and structure stability need further enhanced.…”
Section: Ion‐based Mixed Phosphate Cathodesmentioning
confidence: 99%
“…Recently, Shiprath et al successfully synthesized NFPC nanoparticles with the flower-like hyperbranched structure by a low-temperature ion-thermal method. They employed them as the cathode of the aqueous full sodium-ion battery NaTi 2 (PO 4 ) 3 | Na 2 SO 4 |Na 3 FePO 4 CO 3 , which could provide a discharge capacity of 78.6 mAh g -1 at 0.2 C and 41.62 mAh g -1 at 2 C. [189] The result may inspire the exploration of sodium iron carbonate-phosphates material as anode for aqueous SIBs. [177] Copyright 2016, Royal Society of Chemistry.…”
Section: Kosova Et Al Prepared Nfpc/c By Hydrothermal Synthesismentioning
confidence: 99%